Penerapan Kaidah Al-Tsaabitu bi al-Burhaani Ka al-Tstaabiti bi al-Iyaani dalam Hukum Keluarga pada Penetapan Nasab - Sofie Mayda Sugihfauzia Permana; Izzuma Tasya Rismayanti; Imam Sucipto (CV Rewang Rencang, 2025)
This study discusses the application of the principle of al-Tsābitu bil-Burhāni ka al-Tsābiti bil-‘Iyāni in Islamic family law, especially in determining lineage. This principle asserts that the truth established through valid evidence (burhān) has the same legal force as the truth witnessed directly (‘iyān). The results of the study show that this principle provides a theoretical basis for the recognition of various forms of evidence in determining lineage, both classical ones such as legal marriage, confession (iqrār), and testimony (syahādah), as well as modern ones such as administrative evidence and DNA testing. This principle asserts that as long as the evidence submitted meets the criteria of sharia validity and generates legal certainty (yaqīn al-qāḍī), it is valid to use to establish lineage even without direct observation. Thus, the application of the principle of al-Tsābitu bil-Burhāni ka al-Tsābiti bil-‘Iyāni demonstrates the flexibility of Islamic law in responding to scientific developments and contemporary legal needs. This principle not only strengthens procedural justice in religious courts but also supports the achievement of the objectives of sharia (maqāṣid al-syarī‘ah), particularly in preserving descendants (ḥifẓ al-nasab) and ensuring legal justice for all parties.